Differences of the efficacy values in simple temporary numerical inequality between loser teams in male and female waterpolo Diferencias de los valores de eficacia en desigualdad numérica temporal simple entre equipos perdedores en waterpolo masculino y femenino - J. I. Alonso; P. García; F. Argudo; E. Ruiz (Asociación Española de Ciencias del Deporte, 2010)
With this study has intended to obtain two objectives: the first one, to investigate the efficacy values in the playing microsituations in simple temporary numerical inequality with or without ball possession, and the second, to analyze the relation between these and the condition of loser at the end of the match and in both sexes. For the empirical part were recorded in video all the matches of the X Water polo World Championship celebrated in Barcelona during the month of July of 2003, for its subsequent analysis arrived at by consensus between two specialists previously coached, continuing the guidelines of the observational methodology. Valued themselves, by means of some coefficients, the efficacy in all the playing microsituations in simple temporary numerical inequality with or without ball possession obtaining some efficacy values. In the condition of loser at the end of the match differences were revealed among both sexes in the coefficient of shots exactness without possession (.008); taking as reference a value of p <.05. To conclude, to affirm that in one of the fourteen coefficients of efficacy proposed for evaluate the playing microsituations in simple temporary numerical inequality with or without ball possession in water polo are significant differences among sexes in teams with the condition of loser at the end of the match. Key words: water polo, efficacy, loser, simple temporary numerical inequality. Con este estudio se ha pretendido conseguir dos objetivos: el primero, indagar en los valores de eficacia en las microsituaciones de juego en desigualdad numérica temporal simple con o sin posesión del balón, y el segundo, analizar la relación entre los valores de eficacia en equipos con la condición de perdedor al finalizar el partido y en ambos sexos. Para la parte empírica se filmaron en vídeo todos los partidos de waterpolo del X Campeonato del Mundo celebrado en Barcelona durante el mes de Julio de 2003, para su posterior análisis consensuado entre dos especialistas previamente entrenados, siguiendo las directrices de la metodología observacional. Se valoró, mediante unos coeficientes, la eficacia en todas las microsituaciones de juego en desigualdad numérica temporal simple con o sin posesión del balón, obteniendo unos valores de eficacia. En la condición de perdedor al final del partido se revelaron diferencias entre ambos sexos en el coeficiente de exactitud de lanzamientos sin posesión (.008); tomando como referencia un valor de p<.05. Para concluir, afirmar que sólo en uno de los catorce coeficientes de eficacia propuestos para evaluar las microsituaciones de juego en desigualdad numérica temporal simple con o sin posesión del balón en waterpolo existen diferencias significativas entre sexos en equipos con la condición de perdedor al finalizar el partido. Palabras clave: waterpolo, eficacia, perdedor, desigualdad numérica temporal simple.